2020
DOI: 10.1021/acschembio.0c00049
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Small Molecules Targeting the RNA Repeat Expansion That Causes Genetically Defined ALS/FTD

Abstract: Genetically defined amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), collectively named c9ALS/FTD, are triggered by hexanucleotide GGGGCC repeat expansions [r­(G4C2)exp] within the C9orf72 gene. In these diseases, neuronal loss occurs through an interplay of deleterious phenotypes, including r­(G4C2)exp RNA gain-of-function mechanisms. Herein, we identified a benzimidazole derivative, CB096, that specifically binds to a repeating 1 × 1 GG internal loop structure, 5′CGG/3′GGC, that is for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…37 In addition to the previously identified benzimidazole derivative CB096 29 (Figure 1A), the 2,4-diaminoquinazoline CB253 (Figure 1B) dose dependently displaced TO-PRO-1 from the r(G 4 C 2 ) 8 hairpin. 29 A direct binding assay by microscale thermophoresis (MST) was used to measure CB253′s affinity for 5′-labeled Cy5-r(G 4 C 2 ) 8 , yielding an EC 50 of 30(±4) μM (Figures 1C and S1A). In contrast, no saturable binding was observed for the fully paired RNA r(GGCCC) 10 , d(G 4 C 2 ) 8 , and triplet repeating RNAs 38 These studies afforded an on-rate (k on ) of ∼3 × 10 4 M −1 × s −1 , an off-rate (k off ) of ∼2.3 × 10 −1 s −1 , and a K d of 21(±4) μM (Figure S3A).…”
Section: ■ Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…37 In addition to the previously identified benzimidazole derivative CB096 29 (Figure 1A), the 2,4-diaminoquinazoline CB253 (Figure 1B) dose dependently displaced TO-PRO-1 from the r(G 4 C 2 ) 8 hairpin. 29 A direct binding assay by microscale thermophoresis (MST) was used to measure CB253′s affinity for 5′-labeled Cy5-r(G 4 C 2 ) 8 , yielding an EC 50 of 30(±4) μM (Figures 1C and S1A). In contrast, no saturable binding was observed for the fully paired RNA r(GGCCC) 10 , d(G 4 C 2 ) 8 , and triplet repeating RNAs 38 These studies afforded an on-rate (k on ) of ∼3 × 10 4 M −1 × s −1 , an off-rate (k off ) of ∼2.3 × 10 −1 s −1 , and a K d of 21(±4) μM (Figure S3A).…”
Section: ■ Resultsmentioning
confidence: 72%
“…We previously have shown that model r(G 4 C 2 ) 2 duplexes recapitulate the 1D spectra of r(G 4 C 2 ) 4 and r(G 4 C 2 ) 8 and can allow the identification of a small molecule's binding site. 29 To precisely determine if 1 × 1 GG internal loop sites within the r(G 4 C 2 ) exp hairpin are targeted by CB253, two model duplexes were employed featuring either a single 5′CGG/3′GGC (Figure S8A) or 5′GGC/3′CGG (Figure S8B) motif. Surprisingly, no change was observed in the 1D imino spectra of either construct upon dose-dependent addition of CB253 (Figure S8).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular mechanisms through which these repeat expansions and their quadruplex structures cause the neurodegenerative modifications are not yet known. Nevertheless, some potential therapeutics targeting them are already being investigated [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%